2002
DOI: 10.2486/indhealth.40.291
|View full text |Cite
|
Sign up to set email alerts
|

Metalworking Fluid Hand Dermatitis.

Abstract: In a household appliance plant, several rinse-free lubricating fluids have been used instead of neat mineral oils since 1994: mixtures of isoparaffinic hydrocarbons with 9 to 14 carbons per molecule. As such they denature keratin, irritate and defat the skin, and remove water from it. Work gloves have been worn over plastic gloves and separate, reusable, cotton inner gloves have been added to absorb sweat since skin problems were first recognized in 1994. All 74 males (mean ± SD, 38.8 ± 8.0 years) who work wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Dibasic ester (DBF), which contains dimethyl adipate, dimethyl glutarate, and dimethyl succinate, has been characterized as a mild to severe skin irritant in animals but is not a skin sensitizer (DuPont 1996). Repeated or prolonged dermal contact with isoparaffmic hydrocarbons causes dermatitis (Ueno et al 2002, Mullin et al 1990) and may elicit contact sensitization in rare instances (Mullin et al 1990). Dermal application of croton oil and DMBA produces dermal irritation reactions (Moon et al 2001, Robertson et al 1996, Ruben 1982 and repeat application of DMBA produces a contact hypersensitivity response in the skin (Klemme et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dibasic ester (DBF), which contains dimethyl adipate, dimethyl glutarate, and dimethyl succinate, has been characterized as a mild to severe skin irritant in animals but is not a skin sensitizer (DuPont 1996). Repeated or prolonged dermal contact with isoparaffmic hydrocarbons causes dermatitis (Ueno et al 2002, Mullin et al 1990) and may elicit contact sensitization in rare instances (Mullin et al 1990). Dermal application of croton oil and DMBA produces dermal irritation reactions (Moon et al 2001, Robertson et al 1996, Ruben 1982 and repeat application of DMBA produces a contact hypersensitivity response in the skin (Klemme et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Break-Free CLP is a complex mixture made up of polyalphaolefin oil (65%), synthetic oils, esters and synthetic proprietary ingredients (27%), isoparaffmic hydrocarbons (5%), and dibasic ester (3%). Petroleum distillates (Meyer et al 2000, Nessel et al 1999) and isoparaffinic hydrocarbons (Ueno et al 2002, MuUin et al 1990) have been shown to have dermally irritating properties.…”
Section: Introductionmentioning
confidence: 99%
“…Metalworking fluids are a complex mixture of chemicals that were used for lubricating, cleaning, cooling, corroding and rusting inhibitors, and removing chips in a wide range of processes, such as machining, grinding, metal processing, cutting and shaping metal (1)(2)(3)(4)(5). Mist mineral oils are generated in industrial processes through aeration, contact with fast-moving surfaces and high temperature (6).…”
Section: Introductionmentioning
confidence: 99%
“…Break-Free CLP is a complex mixture made up of polyalphaolefin oil (65%), synthetic oils, esters and synthetic proprietary ingredients (27%), isoparaffinic hydrocarbons (5%) and dibasic ester (3%). Petroleum distillates (Nessel et al, 1999;Meyer et al, 2000) as well as isoparaffinic hydrocarbons (Mullin et al, 1990;Ueno et al, 2002) have been shown to have dermally irritating properties.…”
Section: Introductionmentioning
confidence: 99%